2014
DOI: 10.1002/mnfr.201300458
|View full text |Cite
|
Sign up to set email alerts
|

N-3long-chain PUFA supplementation prevents high fat diet induced mouse liver steatosis and inflammation in relation to PPAR-α upregulation and NF-κB DNA binding abrogation

Abstract: Data presented indicate that n-3 LCPUFAs supplementation prevents liver steatosis and inflammation induced by HFD, with underlying mechanisms involving enhanced PPAR-α signaling and diminished NF-κB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 58 publications
6
57
0
1
Order By: Relevance
“…The activation of PPAR α seems to be a promising target in the treatment of NAFLD because PPAR α is also a key regulator of the genes involved in fatty acid oxidation [3336] and anti-inflammatory effects [37, 38]. Indeed, it has been previously shown that the lack of PPAR α may cause an important hepatic steatosis and liver inflammation [34, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PPAR α seems to be a promising target in the treatment of NAFLD because PPAR α is also a key regulator of the genes involved in fatty acid oxidation [3336] and anti-inflammatory effects [37, 38]. Indeed, it has been previously shown that the lack of PPAR α may cause an important hepatic steatosis and liver inflammation [34, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that PPAR-α plays an important role in the regulation of hepatic lipid metabolism [15,32] and that the inhibition of PPAR-α might induce hepatic steatosis [33] . Thus, we tested the protein level of PPAR-α and found that HFD feeding significantly inhibited the expression of PPAR-α, and that lutein supplementation reversed such inhibition effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Under stimulation (e.g., presence of cytokines), IκBα is phosphorylated, and NFκB can, therefore, translocate to the nucleus, where it induces the gene expression of inflammatory mediators, creating a vicious cycle of inflammation [10]. Feeding mice with an HF diet leads to the activation of NFκB [32], and inhibiting NFκB suppresses the release of proinflammatory cytokines in human adipocytes [33].…”
Section: Discussionmentioning
confidence: 99%
“…PPARα not only increases the expression of IκBα but also inhibits its degradation, blocking NFκB translocation into the nucleus and binding to DNA [32]. PPARβ/δ can inhibit inflammation by inhibiting the activation of NFκB through a mechanism related to ERK1/2 [2].…”
Section: Discussionmentioning
confidence: 99%